Preparation, Properties and Encapsulation of High Thermostability Phase-change Material (Journal of Fiber Bioengineering and Informatics, 2019)
Microcapsules containing phase change materials (PCM) have been attracting much attention due toits applications in many energy storage fields. However, most PCM microcapsules have relatively lowthermostability with an onset decomposition temperature of about 150 ◦C, which to some extent restrictstheir applications. In this study, high chain ester of dodecanol laurate was first synthesized with rawmaterials of 1-dodecanol and lauric acid by esterification reaction under catalysis, and then the ester ascore material was encapsulated using PMMA by emulsion polymerization. The resultant products,including the ester and the PCM microcapsules, were respectively characterized by using infraredspectroscopy (IR), differential scanning calorimeter (DSC), thermogravimetry (TG), laser particle sizeanalyzer and scanning electron microscope (SEM). The synthesized dodecanol laurate have a highpurity according to IR spectrum analysis and suitable phase temperature range of 22-30 ◦C from DSCmeasurement. In addition, the ester also showed good thermal properties with a latent heat of 206J/g, small super-cooling degree of 0.5 ◦C and high thermal evaporation temperature of 220 ◦C, whichwould be very suitable for application in PCM energy storage materials. Using the above ester ascore material, the PCM microcapsules were successfully fabricated by emulsification and polymerizationprocesses. The prepared microcapsules showed perfect spherical shape with size about 865 nm and highheat storage performance with a latent energy of 118 J/g. Owing to high evaporation temperature ofester core material itself and further encapsulation, the prepared PCM microcapsules showed higherthermostability. TG results suggested that the microcapsules had a high onset weightless temperaturewhich was over 252 ◦C, it was a significant increment comparing to those PCM microcapsules reportedby most literatures. Moreover, thermo-regulating cotton fibers were fabricated by using the above PCMmicrocapsules. It’s seen that the PCM microcapsules deposited on the fibers uniformly and the fibershad a latent heat of 20.18 J/g.
Keywords: Esterification; PCM Microcapsules; Thermostability; Latent Heat